Über den Begriff der Gleichgültigkeit in Hegels "Wissenschaft der Logik" und seine Anwendung in der Analyse des Größenbegriffs bei Hegel und Marx - Schlaudt, Oliver (Hegel-Studien, 2013)
I provide an analysis of the term “Gleichgültigkeit” (indifference) in H.s Science of Logic, which, though it constitutes an important technical term, has not yet received much attention in the literature. I fill this gap in three steps: First, since there is no explicit definition, I analyze the actual use of the term in H.s Logic and show that it indicates an equivalence-based abstraction which is structurally equivalent to the concept of definition by abstraction in modern mathematical logic. Secondly, I show how H. makes use of the term “indifference” in his account of quantity in order to resolve a circle he had detected in the classical definition of quantity as “everything which can be augmented or diminished.” He does so by distinguishing between “quantity” and “quantum,” which stand in a relation of indifference. Finally, I shed some light on the reception of this term by analyzing Marx’s use of it in reconstructing the concept of economic value in Capital.